Detailed analysis of in-hospital transmission of SARS-CoV-2 using whole genome sequencing. (January 2023) - O'Connell, L.; Asad, H.; Hall, G.; Jones, T.; Walters, J.; Manchipp-Taylor, L.; Barry, J.; Keighan, D.; Jones, H.; Williams, C.; Cronin, M.; Hughes, H.; et al.
Summary: Background: Hospital transmission of SARS-CoV-2 has proved difficult to control, with healthcare-associated infections troublesome throughout. Aim: To understand factors contributing to hospital transmission of infections, which is necessary for containing spread. Methods: An outbreak of 56 staff and patient cases of COVID-19 over a 31-day period in a tertiary referral unit is presented, with at least a further 29 cases identified outside of the unit and the hospital by whole genome sequencing (WGS). Findings: Transmission is documented from staff to staff, staff to patients, and patients to staff, showing disruption of a tertiary referral service, despite implementation of nationally recommended control measures, superior ventilation, and use of personal protective equipment. There was extensive spread from the index case, despite this patient spending only 10 h bed bound on the ward in strict cubicle isolation and with an initial single target low level ( C T  = 32) polymerase chain reaction test. Conclusion: This investigation highlights how effectively and rapidly SARS-CoV-2 can spread in certain circumstances. It raises questions about infection control measures in place at the time and calls into question the premise that transmissibility can be reliably detected by using lower sensitivity rapid antigen lateral flow tests. We also highlight the value of early intervention in reducing impact as well as the value of WGS in understanding outbreaks.